Data analysis and research for sport and exercise science : a student guide - Williams, Craig A., 1965- (Routledge, 2004)
This is a handbook written for undergraduate sports and exercise science students and should be of particular use to students undertaking research projects and a research-based dissertation. The text is divided into three main areas of Research and Design, Data Analysis and the Interpretation of Findings.